Comparison of gait characteristics between affected and unaffected sides in patients with meniscus lesions: insights from dynamic analysis - Ma, Lin; Xiao, LiuFeng; Huang, Pan; Li, Dianwei; Wang, Yunjiao; Liang, Peiyao; Chen, Yonghua; Guo, Lin (Frontiers in Medicine, 2025)
PurposeThis study aims to elucidate the alterations in gait patterns following knee injuries by comparing the gait analysis of the affected and unaffected sides in patients with meniscus lesions. The findings may provide a valuable reference for the early detection of meniscus injuries.MethodsThe study involved 37 patients diagnosed with meniscus lesions at the Sports Medicine Center of our hospital between December 2023 and November 2024. These patients were confirmed to have meniscus lesions through MRI and arthroscopic surgery. We employed the Dynamic Gait & Posture Analysis System (Shenzhen Xingzheng Technology Co., Ltd.) to analyze three-dimensional gait characteristics, comparing the differences in 3D gait between the affected and unaffected sides.ResultsA total of 37 patients were included in the study, with an average age of 39.24 ± 14.06 years, comprising 18 males and 19 females. Among these patients, 18 had right-sided involvement and 19 had left-sided involvement, with an average disease duration of 20.54 ± 28.59 months. The results of gait phase analysis indicated that the affected side exhibited a shorter duration during the propulsion phase compared to the unaffected side (p < 0.05). Additionally, there were no significant differences in step velocity, step cadence, step length, toe-out angle, and stability support during single-leg stance between the affected and unaffected sides. Analysis of sagittal plane angles between the plantar surface and the ground revealed that the velocity of impact, the maximum dorsiflexion velocity at the beginning of the swing (MDVBW), and the maximum swing velocity on the affected side were all significantly lower than those on the unaffected side (p < 0.05). In contrast, the foot landing angle and angle of propulsion did not show significant differences between the sides. Furthermore, no significant differences were found in the coronal plane angles between the foot sole and the ground measurements, nor in the measurements of foot long axis alignment with the forward direction.ConclusionAmong patients with meniscal lesions, the affected limb showed reduced propulsion-phase proportion, impact velocity, MDVBW, and maximum swing velocity. These side-to-side differences likely reflect sagittal-plane pain-avoidance adaptations.